W (nie)rzeczywistej relacji z Innym, czyli miłość i seks w cyberprzestrzeni - Waszyńska, Katarzyna (Wydawnictwo Naukowe UAM, 2015)
In the age of the Internet a range of interpersonal contacts are made on the Web. The virtual world is a place where people meet, make closer or more distant acquaintances, fall in love, and build relationships. This article is devoted to the topic of online relationships (both romantic and sexual): their phenomenon, specificity, and their influence on reality.
In the (Un)realistic Relation with Others or Love and Sex in Cyberspace
Keywords: cybersex; cyber love; cyber relationships; relationships